Determination of locations of high wall stresses in an abdominal aortic aneurysm (AAA) using computer simulation - Marañon, Dioscoro P. Jr (2005)
From a biomechanical point of view the possible locations of rupture in an abdominal aortic aneurysm (AAA) could be those points which experiences high wall stresses. If these locations of rupture can be identified before they fail anc cause death, proper surgical intervention can be made and possible save lives. At present there is still no fixed method in determining where and when rupture will occur in an AAA.. This study presents a developmental alternative mechanism and attempts to tackle the problem by using images from Computer Tomographt (CT) scans of a patient, which when converted to solid models using the 3-D solid modeling software can then be analyzed using Finite Element Analysis (FEA). As a first approximation solid models wee smoothend by reducing the number of traced point to eliminate excessive curvature, and uniform thickness was assumed for the shell. Material properties such as modulus of elasticity and Poisson's ratio were taken from previous experimental studies. For this initial study, the AAA tissue was assumed to be linear, elastic, isotropic and thin-walled shell. An internal,constant end-systolic pressure was applied to the shell. Both ends of the AAA tissue were constrained in the axial direction, and structural static type of analysis were employed. The von-Mises stresses and displacements were solved at different parts of the AAA tissue using finite element method. Previous studies focused on factors that cause rupture such as diamter of bulge, asymmetry, volume, degree of curvatrure, high stresses, surface geometry, degree of twist and inflection points. The results of this study showed that combined factors of thickness, internal pressure, cocavity factor, strain or degree of expansion, tist and bending due to geometry need to be considered in determining the possible locations of rupture in an AAA. The framework presented in this study can possibly be initially used in monitoring of patients with AAA.